Competitiveness in Central-Europe : What Has Happened Since EU Accession? - Allard, Celine (Washington, D.C. : International Monetary Fund, 2009)
Since EU accession, trade flows have exhibited strong dynamics in Central-Eastern Europe (CEE). During the period leading to the current global turmoil, the region has also experienced continuous exchange rate appreciation and rapid FDI inflows, both likely to have affected these countries' competitiveness. This paper describes how the determinants of exports and imports have evolved in CEE countries over 2002-07 and econometrically derives their contribution to trade, with a view to assessing competitiveness developments. The analysis reveals that the global and domestic upswings, along with rising trade market shares, go a long way toward accounting for trade developments in CEE countries until 2007, pointing to continuous nonprice competitiveness gains. It also finds that exchange rate appreciation did not unduly weigh on export and import growth, suggesting that most of it reflected an upward movement in its equilibrium value. While the region entered the current period of global slowdown from a strong competitiveness position, the crisis also exposed the vulnerability of its heavy reliance on global demand to a trade shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet